Distinct lignocellulolytic enzymes produced by Trichoderma harzianum in response to different pretreated substrates. (June 2023) - Zhang, Yu; Wang, Ruonan; Liu, Liang; Wang, Entao; Yang, Jinshui; Yuan, Hongli
Graphical abstract: Highlights: Distinct pretreated substrate can be used as inducer for specific enzyme production. Formulation of cocktails with distinct components improved the hydrolysis efficiency. 100% glucose and xylose of ultrafine grinding treated corn stover were obtained. Abstract: In order to optimize the composition of enzyme cocktail for improving the hydrolytic efficiency of lignocellulose, different substrates were tested as inducers for producing lignocellulolytic enzymes by Trichoderma harzianum EM0925 in this study. As results, ultrafine grinding or steam explosion pretreated substrates can induce T. harzianum EM0925 to secret holo lignocellulolytic enzymes; acid treated substrate can induce cellobiohydrolase; while alkali or sodium chlorite treated substrates can induce β-xylosidase specifically. Furthermore, the combination of enzyme cocktails with different hydrolysis characteristics can further improve the hydrolysis efficiency, since 100% yields of glucose and xylose were obtained simultaneously from ultrafine grinding treated corn stover at low enzyme dosage (1.2 mg proteins/g substrate). This study for the first time demonstrated an effective solution that specific-pretreated substrates can be used as inducers for specific enzyme production by T. harzianum, which provided new idea and potential strategy for the construction of highly-efficient lignocellulolytic enzyme cocktails.